Police Deviance and Corruption in the United States and in Portugal: Identifying Criminological Trends and Theoretical Explanations - James F. ALBRECHT; S. de MELO BANDEIRA, Gonçalo (Revista Jurídica Portucalense, 2023)
Law enforcement is considered a noble profession in many democratic countries. Occasionally, however, several police officials have been observed engaging in corrupt, criminal and abusive activities. Unfortunately, when Transparency International conducted a recent annual survey to identify which institutions the public viewed as being most corrupt, the police and elected government officials were tied as being perceived as the most deviant of all public entities. Approximately 36% of people globally responded that they perceived the police as being highly corrupt. The recent public demonstrations globally demanding police reform, and, more disturbingly, the calls to “defund the police” in many major American cities are another indication that police deviance is a major concern internationally. In order to better understand the sociological theories associated with police deviance and the related trends and patterns experienced in the United States and Portugal, two highly respected western democracies, these phenomena will be outlined and contrasted. After establishing a clear typology for police deviance, criminological explanations will be identified for specific categories of misconduct. The resultant comprehensive insight of the underlying foundations of these unacceptable acts of law enforcement misconduct will result in detailed practical recommendations for enhancing ethical conduct and professionalism within the critical field of public policing.